Drivers of species richness and abundance of marine macrophytes on shallow tropical reefs of north‐western Australia. (9th December 2018) - Olsen, Ylva S.; Mattio, Lydiane; Zavala Perez, Andrea; Babcock, Russ C.; Thompson, Damian; Haywood, Michael D.E.; Keesing, John; Kendrick, Gary A.
Abstract: Aim: Marine macrophytes are important components of tropical reefs that are influenced by environmental conditions and biotic interactions. Here, we aimed to identify the factors that shape macrophyte communities on shallow reefs in a region with limited anthropogenic impacts, but that is influenced by periodic disturbances from cyclones and marine heatwaves. Location: Pilbara coast, Western Australia. Methods: Macrophyte species richness and biomass were assessed at 75 shallow reefs along 300 km of shoreline in November 2013 and May 2014. The influence of 28 predictor variables including seascape descriptors, physico‐chemical variables, and herbivore abundances were evaluated using distance based linear models (DistLM), redundancy analyses (dbRDA), and full‐subsets multiple regressions. Results: We identified 188 macrophyte species; 60% were Rhodophyta, whereas Phaeophyceae made up 67% of the biomass. Macrophyte assemblages did not show any broad‐scale patterns but a number of key drivers were identified, including sea surface temperature, salinity, and sediment uniformity. Two of the main predictors of macrophyte abundance and species richness were rugosity and coral cover rather than herbivory, unlike what has been demonstrated for many reefs globally. Availability of space therefore appears to be a major factor on these reefs and it is possible that macrophytes benefit from periodic disturbances as they can free up space through physical removal of organisms. Main conclusions: Macrophyte assemblages along the Pilbara coast show no distinct large‐scale patterns; instead, local biotic and environmental drivers such as rugosity appear to be structuring assemblages. We propose that natural disturbance plays a key role on these shallow reefs by increasing substrate availability. Data on the long‐term community structure of macroalgae, in particular how communities respond to heatwaves and cyclones, would improve our ability to manage these reefs and predict potential "phase shifts" which can have severe ecological and economic consequences.